Information security aligned to enterprise management - Abdullah, Istikoma; Fakhri, Nurul Fahimah; Mastoi, Qurat-ul-ain; Ibrahim, Jamaludin (medi+WORLD Internationa, 2015)
This paper illustrates business aligned security approach as a key element of an enterprises’s overall business strategy. Business information security is a crucial concern in enterprise management for risk handling operation. The modern era of technology security for businesses is increasingly recognized especially in business strategies. Disconnection of information security procedures and commercial strategic business objectives effects to control security spending and their risk, incidents and losses. Operational enterprise system requires aligning security practices through embedding information security risk management into the organization, however it faces major challenges to support and enable the business. Alignment security in business process is one of the biggest challenges in good organization as it needs support re- sources and time management and ways to align security to overcome business objectives. Thus, an information security management role is important as a guideline to execute Business Information Security. In addition, the systematic security management introduces a business model for critical information infrastructure protection. Organization design and strategy, people, process and technology are the elements of the model which play an effective role in information security but it requires a balance among them.